The Effect of Using Context-Based Physics Learning Videos on Critical Thinking Skills of XI Grade High School Students - Rezza Septia Sari; Desnita Desnita (Jurnal Ilmiah Pendidikan Fisika, 2023)
Education in the 21st century demands the readiness of students to face the ever-evolving era. This study aims to determine the effect of using context-based physics learning videos on the critical thinking skills of class XI students at SMA N 1, Suliki District. Students' critical thinking skills at SMA N 1 Suliki District are still low because the use of instructional media has not honed students' critical thinking skills. One solution to this is through the use of context-based physics learning videos. This type of research is quasi-experimental. Posttest-Only Control Design research design. The population in this study were all students from class XI SMA N 1 Suliki District for the 2021/2022 academic year. The process of taking samples is carried out through a purposive sampling technique, namely choosing two classes with the same average. The data collected is from students' critical thinking skills, including "interpretation, analysis, evaluation, and inference". The data was obtained using a written test instrument in the form of essay questions with as many as 8 items. The data analysis technique used in the hypothesis test is the t test. Based on the results of data analysis, it was found that the average ability of students' critical thinking for the experimental class was higher than the control class. The results of the t hypothesis test obtained a calculated value with a magnitude of 2.729 and a critical value for the significance level at α = 0.05, and 67 degrees of freedom obtained a value of 2.293. Because the calculated value is greater than the critical value, the hypothesis is accepted at a significant level of 0.05. Based on the results obtained, it can be concluded that using context-based physics teaching videos has an effect on the critical thinking skills of class XI students at SMA N 1 Suliki District.